Metabolic Syndrome, depression and patient safety culture in Mexican resident physicians - Gaona-Valle, Laura Soraya; Velázquez Arriaga, Ariadna; Michel Ramírez, José Manuel; Castro-Quezada, Itandehui; Zúñiga Torres, María Guadalupe; López García, Alma Edith (Medicina e Investigación Universidad Autónoma del Estado de México; Vol. 9 Núm. 2 (2021): Medicina e Investigación (julio-diciembre), 2021)
Background: Medical residence can affect the well-being and health of resident physicians (rp), which are directly related to the quality of medical care and patient safety. El objective was to identify the prevalence of metabolic syndrome (MetS), depressive symptoms, and evaluate the culture of patient safety in resident physicians. Methods: Cross-sectional analytical survey of 106 physicians residing in 13 medical specialties of a public hospital in Mexico. MetS was defined according to who criteria and depressive symptoms using the cesd-r scale; the culture of patient safety was evaluated with the Spanish version of the Hospital Survey on Patient safety. Results: 53.7% had a combined prevalence of overweight/obesity and insulin resistance was found in 33%. 8.5% of rp had prediabetes and 2.5% diabetes. 23.6% of the sample presented two MetS components. The prevalence of MetS was 8.5% and depressive symptoms were found in 21.7% of rp. The evaluation of the culture of patient safety showed strength in the dimensions of teamwork in the unit-service, organizational learning- continuous improvement, expectations and actions of the direction and frequency of reported events, perception of patient safety culture was found in 8/10 rp. Conclusions: A high prevalence of cardiometabolic alterations and depressive symptoms was found in Mexican rp. It is necessary to promote self-care for health and to strengthen the concept of patient safety culture among resident physicians.